Integrating Artificial Intelligence into Plant-Based Diet Programs: The Bethsaida Hospital Experience - Mulijono, Dasaad (Cardiology and Cardiovascular Medicine, 2025)
The convergence of artificial intelligence (AI) and nutritional medicine represents a frontier in the evolution of precision healthcare, offering unprecedented potential to address the global burden of chronic diseases. At Bethsaida Hospital in Indonesia, under the visionary leadership of Prof. Dasaad Mulijono, AI has been seamlessly integrated into a clinically validated Whole Food Plant-Based Diet (WFPBD) program designed not only to prevent but also to reverse prevalent noncommunicable diseases such as cardiovascular disease, type 2 diabetes mellitus (T2DM), obesity, hyperlipidaemia, and hypertension. This article delineates the strategic deployment of AI across multiple dimensions of care, including individualized patient education, dynamic menu generation, real-time metabolic monitoring, and intelligent interpretation of laboratory biomarkers. The system enables fully personalized nutritional recommendations tailored to each patient's caloric expenditure, macronutrient balance, micronutrient sufficiency (including protein, omega-3 fatty acids, vitamins, minerals, and fibre), and specific clinical goals. Remarkable clinical improvements have been observed in key biomarkers, including reductions in trimethylamine N-oxide (TMAO), enhanced nitric oxide (NO) bioavailability, and favourable modulation of cholesterol levels, blood glucose, blood pressure, and body mass index (BMI). The integration of AI not only amplifies patient engagement and adherence but also enhances clinical efficiency and scalability. This model illustrates how AI can bridge the gap between scientific knowledge and clinical practice in nutrition, providing a replicable, data-driven framework for sustainable, preventive, and personalized lifestyle medicine globally.